2022
DOI: 10.3389/feduc.2022.880990
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Teaching and Learning English-Speaking Skills: A Review and Bibliometric Analysis

Abstract: This study conducted a comprehensive historical review and bibliometric analysis of the literature on English-speaking (ES) education and mapped the current state of the field, trends, and emerging topics, as well as identified gaps where further research is needed. We retrieved 361 sample documents on ES teaching and learning in Scopus (2010–2021) under certain conditions and analyzed the extracted data using Excel and VOSviewer 1.6.17 from the perspectives of the number of yearly publications, countries, aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The reason why Scopus chosen was that is userfriendly in the sense that information can be conveniently retrieved through string retrieval. This study replicated the methodologies used by Lázaro (2022), Wang & Leong (2022), and Kaya and Erbay (2020). This study was conducted around RQs after the identification of some keywords as conditions for data mining.…”
Section: Article Selection and Identificationsupporting
confidence: 81%
“…The reason why Scopus chosen was that is userfriendly in the sense that information can be conveniently retrieved through string retrieval. This study replicated the methodologies used by Lázaro (2022), Wang & Leong (2022), and Kaya and Erbay (2020). This study was conducted around RQs after the identification of some keywords as conditions for data mining.…”
Section: Article Selection and Identificationsupporting
confidence: 81%
“…Scopus is one of the biggest databases for bibliographic information in the social sciences. It has been incorporated into numerous prior bibliometric analyses in the different fields of education research (Lam & Habil, 2021; Wang et al, 2022; Yoopetch, 2019 ) . To ensure that all publications were consulted, the authors of this study used a number of search protocols covering ELT research.…”
Section: Methodsmentioning
confidence: 99%
“…The use of bibliometric analysis to reveal the research direction has gained popularity in different fields. For example, So (2016)investigated the trends of research on business reporting language; Farrukh et al (2023) identified trends and patterns in pro-environmental behavior research; Hashim et al (2018) studied on trends on the use of social media for teaching and learning at higher education; Muritala and Maria-victoria (2020) traced out online reviews research in tourism and hospitality and Wang et al (2022) examined studies of speaking skills teaching and learning. Thus, there is a need to conduct a bibliometric analysis for identifying the trends of the research in ELT.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important that these interactions be presented at the student's proficiency level (Ma, 2010;Qiu & Xu, 2022). To illustrate, participants would have only partial information available to finish the task, but they would have opportunities to generate meaningful negotiation (Brunfaut & Révész, 2015;Wang, Abdullah, & Leong, 2022). Additional interactions could include having students speak to each other while participating in group activities.…”
Section: Review Of Literature Efl Listening and Speakingmentioning
confidence: 99%